Research progress on the role and mechanism of circadian clock gene PER1 in the occurrence and development of multiple diseases - Zhao, Yuxiang; Li, Yujin; Lu, Tingting; Huang, Xinyue; Chen, Kerui; Tan, Lina; Gao, Lihua (Frontiers in Immunology, 2025)
Circadian rhythm, an inherent 24-hour periodic rhythm in organisms, is regulated by circadian clock genes. As a key component of the transcription-translation feedback loop, the core circadian gene period (PER) 1, not only maintains circadian rhythm homeostasis but also plays a significant role in the pathophysiological processes of various human diseases. This review summarizes the biological characteristics and regulatory mechanisms of PER1, as well as its roles and molecular mechanisms in cardiovascular diseases, nervous system diseases, metabolic disorders, immune-related diseases, and tumors. In cardiovascular diseases, PER1 helps regulate blood pressure, renal function, and vascular inflammation. In the nervous system, it influences ischemic brain injury, sleep homeostasis, and neurodegenerative diseases. In metabolic disorders, PER1 modulates endocrine function, glucose-lipid metabolism, and energy balance. In immune-related diseases, it regulates immune cell functions and inflammatory signaling. In tumors, PER1 has tumor-suppressive effects, with low expression correlating to poor prognosis. This review highlights the critical role of PER1 as a core circadian gene in maintaining physiological homeostasis and regulating disease progression, providing a comprehensive perspective for understanding its complex functions in physiological and pathological processes, offering new insights for developing precision therapies targeting PER1 and its associated signaling pathways.